Pendidikan Kesehatan tentang Pencegahan Stunting Balita di Wilayah Puskesmas Betungan Kota Bengkulu - Elsi Rahmadani; Pawiliyah Pawiliyah; Suryani Suryani; Novi Ade Suryani (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background : Stunting is a problem because it can cause morbidity, death, slow down the process of motor development and hinder the mental growth process of sufferers. Stunting not only interferes with physical growth but also in other growth such as mental, cognitive and intellectual children. The purpose of this community service is to conduct socialization and counseling in an effort to prevent stunting in the Betungan Health Center work area, Bengkulu City. The implementation method is by counseling about stunting in children. This Community Service activity was carried out at the Betungan Bengkulu Health Center. The time for implementation is in November 2022. The participants in this community service activity are mothers who have toddlers at the Bentungan Health Center in Bengkulu City with a total of 20 people. Activities are carried out in stages (1) providing an explanation of the material to be provided and the purpose of the activity; (2) provide knowledge about child stunting and its prevention. The results of this activity show that there is an increase in public understanding of what stunting is, the causes of stunting, the dangers of stunting for the short and long term as well as growing awareness in overcoming the effects of stunting so as to minimize the occurrence of stunting in children. Keywords: Children, Stunting, Health Education